Security and Safety: Legal Protection of Travelers - Ashifa Yulian Devi; Andin Rusmini (Saniya Institute, 2023)
Tourism is indispensable for a country because it is one of the contributors to the country's foreign exchange. This study aims to determine the legal protection of tourists. The method used in the research is normative juridical with legal materials in the form of primary and secondary law, with analysis techniques using qualitative normative. In Indonesia, it is the second largest after the plantation commodity. Despite being the largest, there are several problems that occur related to safety and comfort in traveling such as price discrimination and street crime. Therefore, the Indonesian government is obliged to provide legal protection to all tourists so that no one suffers losses both in terms of tourists, local residents and the government.